“DÜNYAYA ORMAN DENİR” ADLI ROMANIN ÇEVRECİ ELEŞTİRİ BAĞLAMINDA BİR İNCELEMESİ - Kevser ATEŞ (Fırat University, 2019)
The Word for World is Forest is one of the contemporary science fiction novellas that focuses on the possible catastrophic results of anthropocentric attitude of people towards nature in the future. Athshean people seem to have built the perfect future that nature lovers want to achieve, but this dream world faces some unpredictable nightmares when they meet yumens which they call people coming from earth. Though this novella is known to be Ursula K. Le Guin’s way of reacting against Vietnam war through the example of greedy, cruel and violent military attacking on the innocent people of the new planet they have discovered, this study aims to analyse this work from an ecocritical perspective as it shows a great contrast between yumens that have turned their world into a desert after long years of insensible consumption of its natural resources and Athshean people who have succeeded in building a balance between their culture and nature. Instead of learning from these peaceful people who have established a community without disturbing the balance of nature, military people keep cutting trees and enslaving natives as they did in their previous planet without regarding the failure they had in the end. In order to protect their planet, Athshean people who have never experienced such violence in their towns before which are governed by women, decide to attack them under the guidance of Selver, who has escaped from yumens enslaving him. The Word for World is Forest illustrates what we may encounter in the future if the social and ecological consequences of our interaction with nature are not given enough consideration today.